Revealing Antidepressant Mechanisms of Baicalin in Hypothalamus Through Systems Approaches in Corticosterone- Induced Depressed Mice - Zhang, Kuo; He, Meiyao; Wang, Fan; Zhang, Haotian; Li, Yuting; Yang, Jingyu; Wu, Chunfu (Frontiers in Neuroscience, 2019)
Baicalin, the main active flavonoid constituent of Scutellaria baicalensis Georgi, has been reported to exert antidepressant effects. Hypothalamic-pituitary-adrenal (HPA) axis plays important roles in depression. However, antidepressant effect and mechanism of baicalin on HPA axis in hypothalamus are still unknown. In present study, we find baicalin significantly attenuates the increase of immobility time in tail suspension and forced swimming, improves the decrease of spending time in open arms, and restores the aberrant negative feedback of HPA axis in chronic corticosterone (CORT)-induced depressed mice. Moreover, proteomics finds 370 differentially expressed proteins after baicalin treatment, including 114 up-regulation and 256 down-regulation in hypothalamus. Systems biology analysis indicates the functions of differentially expressed proteins focus on phosphoserine binding and phosphorylation, especially participate in GR signaling pathway. Finally, our findings demonstrate that baicalin normalizes hypothalamic GR nuclear translocation via reducing GR phosphorylation to remodel negative feedback of HPA axis in CORT-induced mice.